What do coaches want to know about sports-related concussion? A needs assessment study - Sullivan, L.; Molcho, M. (Journal of Sport and Health Science, 2018)
Purpose: This study aims to identify the concussion-related training and education needs of Gaelic Athletic Association (GAA) coaches in Ireland, as well as the preferred method of concussion education delivery. Methods: We used a self-report questionnaire to collect data from a convenience sample of 108 GAA coaches in Ireland. Data were captured on (1) informational needs and desires, (2) preferred methods of delivery, and (3) concussion practices and procedures. Questionnaires were completed electronically from June 3rd-September 29th, 2015. Results: Coaches indicated that they were most interested in receiving information about the (1) signs and symptoms of concussion, (2) assessment of concussion, and (3) return-to-play guidelines. Over two-thirds of participants indicated that in-person training would be the most effective mode of delivery of concussion education for this population. Additionally, only 10% coaches reported that before the start of the season they talked to their athletes about concussion management and safety, and this was more common among coaches who reported being formally educated about concussion. Conclusion: Our findings reveal a disconnect between the concussion education needs and the education that is currently provided to GAA coaches, in terms of content and delivery modality. Our results suggest a need for a multifaceted approach to concussion education, tailored to the needs and learning preferences of the target population.